Crescimento, fisiologia e produção de maracujazeiro amarelo irrigado com água salina e adubado com cálcio e esterco - Dias, Jefferson Alves (2021)
The high saline content of irrigation waters results in losses of water availability to plants, which in traditional irrigated cultivation further inhibits growth, yield and compromises the quality of production obtained by the majority of crops of economic importance in the world, including the passion fruit that arrives at a national productivity of 15 t ha-1. This inconvenience demands management technologies that make it possible to maintain the property with income throughout the year. In this context, the objective was to use saline water to irrigate yellow passion fruit, providing calcium to the plants at the time of greatest nutrient extraction by the crop, during the growth and development of the fruits, and mitigating the aggressiveness of the salts, through the action of the applied organic matter. to the soil when preparing holes and covering. The treatments were installed in randomized blocks with four replications using the split-plot scheme, in a 2x(2x2) factorial arrangement, with the main plot being non-saline and saline water (electrical conductivity 0,5 and 4,5 dS m-1) and the subplots the combinations of calcium source (dolomitic limestone and calcium nitrate) and cattle manure (without and with). Calcium was applied 40% when preparing the pits and the remaining 60% was divided into four applications of 15% at 70, 100, 130 and 160 days after transplanting the seedlings (DAT). Bovine manure was applied 50% in the preparation of the pits and the remainder in full flowering of the plants in an area of 0,5 m2, with a total dose of 7,6 kg. Weekly, starting 15 days after transplanting the seedlings (15 DAT), plant growth was measured. When they were in full bloom, a physiological assessment was carried out, the fruits per plant were harvested when they had at least 50% of their yellow skin on, packed in plastic boxes for later weighing and productivity quantification. The data were subjected to analysis of variance using the F test (p≤0.05), using the SAS® University Edition software. The sigmoidal model that best fits for evaluating the growth in diameter of passion fruit plants is Richards, taking into account the evaluative indices; Saline irrigation water influences the growth in diameter of passion fruit plants; Calcium nitrate and organic matter can promote greater growth in diameter and height in passion fruit plants. Irrigation water with an electrical conductivity of 4.5 dS m-1 harms the photosynthetic processes of passion fruit plants; Calcium, regardless of the source, can be used to mitigate the degenerative effects of stress caused by salts in irrigation water on passion fruit crops; Manure promotes benefits for net photosynthesis, water use efficiency and internal carboxylation efficiency of passion fruit when irrigated with non-saline water; Productivity is not affected by the factors evaluated.